The Impact of Oil Prices on Stocks Markets: New Evidence During and After the Arab Spring in Gulf Cooperation Council Economies - El-Chaarani, Hani (International Journal of Energy Economics and Policy, 2019)
This study investigates the impact of stock price fluctuations on stock markets in six countries in Gulf Cooperation Council (Saudi Arabia, Kuwait, Oman, Bahrain, United Arab Emirates (UAE) and Qatar) during and after the recent geopolitics conflicts, known as Arab Spring, from January 2011 to December 2017. Two statistical models were implemented to measure the relationship between oil price fluctuations and stock markets returns. The logistic smooth transition model (LSTR) was implemented to measure the relationship between oil price direction (positive/negative) and stock markets returns. The exponential smooth transition model (ESTR) was applied to capture the relationship between the magnitude of oil price fluctuations (small/large) and stock markets returns. The results reveal several asymmetrical results of oil price directions (positive/negative) on stock markets returns in some GCC countries. In Saudi Arabia, Kuwait and Bahrain, the negative oil price fluctuations have larger impact on the returns of stocks markets than positive oil price fluctuations. The results reveal also that the existence of political instability increases the sensitivity of stock markets returns on negative oil price shocks. In addition, the results of ESTR model do not reveal any asymmetrical relationship between the magnitude of oil price changes and stock markets returns in GCC region except Oman. A high level of oil price shocks has larger impact on Omani stock market returns than small oil price shocks. Keywords: Oil prices, Stock Markets, Arab Spring, Geopolitical conflicts, Gulf Cooperation Council JEL Classifications: E02, E44, E6, G18, Q41 DOI: https://doi.org/10.32479/ijeep.7978